A1 4 It’s Blind of a Funny Story - Bujdoso, Kieran; Stentiford, Madeleine; Holmes, Pippa; Tasyaka, Andrea (Physics Special Topics, 2024)
In this paper we analysed the observational abilities of the astronomers in the film ’Armageddon’, where they only identify the asteroid hurtling towards them 18 days before its impact. We found that based on existing infrastructure at the time, they should have had over 6.6 years of notice in order to formulate a response. Additionally, modern technology would spot the asteroid with up to 70,000 years’ notice.